Desenvolvimento e caracterização de geleia de feijoa (Acca sellowiana) com redução de teor de açúcar - Menin, Daiana (2019)
The development of new products conditions the consumer market daily, the search for innovative, practical products with high nutritional value and pleasant sensory aspect makes the industries, institutes and universities increasingly arouse interest ininnovation. Jam is widespread in the consumer market, given the numerous raw material resources and formulation diversity, making it an important strategy for adding value and promoting fruit consumption, including those little known, not just for nutritional value, but also from the perspective of representing an increase in agricultural production, expansion of industrial activity and export potential. When considering the search for foods with a healthier appeal, it is necessary to insert food products in the market that present benefits to the consumer's health. Thinking about it and the diversity of fruits, the valorization and dissemination of native fruits, this study aimed to study the raw material feijoa(Acca sellowiana), develop and characterize four formulations of jam from the pulp: common (F1), extra (F2), with reducedsugar content (F3) light(F4), defined in relation to the proportion of pulp and sugar (%): 40-60; 50-50; 60-40; 70-30 respectively. Fruits were evaluated for biometric, physicochemical and biochemical variables. The jam was characterized by physicochemical, microbiological and biochemical standards. In addition, both fruit and jam were identified and quantified for sugar content (sucrose, glucose and fructose) by high performanceliquid chromatography (HPLC). The formulations were also evaluated for sensory acceptance and purchase intention tests. The data from this study were statistically analyzed using the Statistica® version 7 software. The fruits presented an average mass yield value of 43.55% and a length / diameter ratio of 1.22cm. The greenish-colored fruit peel (h* 123.67), and as a texture attribute the strength to break the epidermis had a hardness of 8.99 N. The pulp has a yellowish cream color (h * 92.13) and soft texture, with penetration force of 0.21N. The values for the parenchyma were between the peel and the pulp for color (h * 91.14) and texture (4.69 N). Fresh pulp presented pH, SST (ºBrix), ATT (% citric acid) and water activity values of 3.58, 10.65 ºBrix, 0.60% and 0.948, respectively. The average values obtained for sucrose were 3.99%, glucose 1.53% and fructose 2.08%. As for the results of phenolic compounds and pulp antioxidant activity with water As for the results of phenolic compounds and antioxidant activity of the pulp with the 50% v / v ethanolic solution, the total phenolic compounds showed 465.30 mg EAG g-1, DPPH with 1743.09 μmol TEAC gˉ¹, ABTS 4496.82 μmol of TEAC gˉ¹ and FRAP 9910.32 μmol Fe 2+ gˉ¹.For the attributes physicochemicalx in the jam formulations were found to have pHvalues of 3.03, 2.87, 2.93, 3.03, SST of 69%, 69%, 57%, 47% and for ATT of 0.49%. 0.75%, 0.86%, 1.05%, water activity with values of 0.790, 0.750, 0.860 and 0.890, respectively for F1, F2, F3 and F4. The hue of the jellies showed colors close to reddish yellow,(h* values of 74.33, 79.51, 79.80 and 71.52 for F1, F2, F3 and F4) and compressive strength (Hardness) behaved in relation to the proportion of added sugar being 6.80, 2.32, 0.44 and 0.24N for formulations 1 to 4, respectively. For the phenolic compounds and antioxidant activity, the results of total phenolic compounds for the elaborated formulations ranged from 50.69 to 69.36 mg EAG gˉ¹. For antioxidant capacity by the DPPH method, 371.01 to 435.96 μmol of TEAC gˉ¹, ABTS between 1053.15 to 1838.53 μmol of TEAC gˉ¹, and FRAP 1345.47 to 1892.43 μmol Fe 2+ gˉ¹ for the four elaborate jellies. As for microbiological standards, all formulations had results in accordance with current legislation. It was found that the values of the hedonic scale of the attributes match the percentage of responses achieved in the purchase intention test, and for F1, all sensory results reached a higher percentage when compared with the other formulations. Corroborating these results, F1 reached the minimum acceptance index (AI) required (70%) for all variables, obtaining an AI for the overall impression of the product was 80.33%. Despite not being classified with a minimum percentage of AI for all variables, F3 (with a reduction of 17.39% of sugar) showed good results throughthe tests applied.The knowledge of the nutritional and nutraceutical potential of fruits and derivatives of feijoa may allow access to new markets with differentiated products.The results of thephysical-chemical characterization agreed with those of similar studies reported in the literature. The microbiological evaluation showed the product to be commercially sterile, indicating that the heat treatment was efficient in maintaining the microbiological stability of the product. Increasing the supply of healthier foods should be a goal in the development of new products contributing to the reduction of sugar consumption, and modification of the population food habits, overcoming the difficulties of sensory acceptance.